Methods to extract the exopolymeric matrix from biofilms: a comparative study - Azeredo, Joana (1998)
To study biofilm composition a previous extraction method is required to separate cells from the matrix. There are several methods reported in the literature, however they are not efficient or promote leakage of intracellular material. In this work several extraction methods were assayed in mixed culture and pure culture biofilms and their efficiency was evaluated by the amount of organic carbon, proteins and intracellular material extracted. The results showed that extraction with glutaraldehyde 3% (w/v) was the most suitable method, extracting great amounts of organic carbon without promoting cell lysis or permeabilization. Glutaraldehyde is a bifunctional reagent that binds to cell walls avoiding their permeabilization and the biofilm matrix is solubilized in the solution.